Intrapartum Amnioinfusion in Meconium-Stained Amniotic Fluid- A Randomized Control Study in A Tertiary Care Hospital - Vachhani, Ashvin D; Shah, Jitesh M; Goel, Garima S; Mehta, Meghana N; Desai, Archish I; Dalal, Malati T (National Journal of Community Medicine, 2015)
Objective: The study was undertaken to evaluate maternal and Perinatal outcomes following transcervical intrapartum amnioin- fusion in women with meconium stained amniotic fluid. Methods: A randomized control study was conducted on 200 women with moderate to thick meconium stained amniotic fluid during labor. Group A (study group) of 100 cases received amnio- infusion. Group B (control group) of 100 cases received standard obstetric care. Fetal heart rate monitoring was done using cardioto- cography. Results: 66% of women were in the age group of 21-25 years. Av- erage cervical dilatation at detection of meconium and detection of meconium to delivery interval was similar in both groups. In the study group, 68% women had normal vaginal delivery as com- pared to 49% in the control group (p<0.01). Operative delivery was required in 32% and 51% cases in groups A and B respectively. Me- conium aspiration syndrome was developed in 5% cases in group A and 15% cases in group B (p=0.02, Odds ratio 0.29 (0.1-0.85)). There were no differences in Apgar scores, NICU admissions and Perinatal mortality between two groups. No any maternal compli- cations were noted due to amnioinfusion. Conclusion: Intrapartum amnioinfusion in meconium stained am- niotic fluid is simple, safe and inexpensive intervention to reduce the rates of meconium aspiration syndrome and its complications.